Diterpenoids and Their Glycosides from the Stems of Tinospora crispa with Beta-Cell Protective Activity - Lam, Sio-Hong; Liu, Hui-Kang; Chung, Shih-Yuan; Chang, Jia-Ling; Hong, Mao-Xuan; Kuo, Sheng-Chu; Liaw, Chih-Chuang (Journal of natural products (Washington, D.C.), 2023)
Seven previously undescribed diterpenoids, tinocrisposides A–D (1–4) and borapetic acids A (5), B (6), and C (7), together with 16 known compounds, were isolated from the stem of Tinospora crispa (Menispermaceae). The structures of the new isolates were elucidated by spectroscopic and chemical methods. The β-cell protective effect of the tested compounds was examined on insulin-secreting BRIN-BD11 cells under dexamethasone treatment. Diterpene glycosides 12, 14–16, and 18 presented a substantial protective effect on BRIN-BD11 cells treated with dexamethasone in a dose-dependent manner. Compounds 4 and 17 with two sugar moieties exhibited clear protective effects on β-cells.